Return to the Origins? Cultural Genocide between Political Debate and the Evolution of International Institutions (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
This article describes the historical debates regarding the definition of cultural genocide and the failed attempts to introduce it as a distinct crime under international law. Though the protection of cultural heritage has been included in several international regulations and it is now under the jurisdiction of international courts, the lack of a specific identification of cultural genocide as a crime against humanity still represents a subject of interest for jurists. The aim of this study is to rediscuss Raphael Lemkin’s work and its impact in the following years, including the activity of international tribunals when dealing with the destruction of cultural heritage. Cultural genocide is today discussed as a possible solution to the widespread necessity to prevent all threats posed to diversity and multiculturalism, and a critical analysis of its historical evolution is essential to understand its relevance both under a political and a legal point of view.
Keywords: Cultural genocide; Cultural heritage; International law; Protection of minorities